Foundations of embodied learning : a paradigm for education - Nathan, Mitchell J. (New York, NY : Routledge, 2022)
"Foundations of Embodied Learning advances learning, instruction, and the design of educational technologies by rethinking the learner as an integrated system of mind, body, and environment. Body-based processes-direct physical, social, and environmental interactions-are constantly mediating intellectual performance, sensory stimulation, communication abilities, and other conditions of learning. This book's coherent, evidence-based framework articulates principles of grounded and embodied learning for design and its implications for curriculum, classroom instruction, and student formative and summative assessment for scholars and graduate students of educational psychology, instructional design and technology, cognitive science, the learning sciences, and beyond"--
Keywords: Instructional systems -- Design; Human body in education; Educational psychology; Educational technology; EDUCATION / Educational Psychology; EDUCATION / Distance Education & Learning; PSYCHOLOGY / Cognitive Psychology